Optical properties and spectroscopy of nanomaterials - Zhang, Jin Zhong (World Scientific, 2009)
Optical properties are among the most fascinating and useful properties of nanomaterials and have been extensively studied using a variety of optical spectroscopic techniques. A basic understanding of the optical properties and related spectroscopic techniques is essential for anyone who is interested in learning about nanomaterials of semiconductors, insulators or metal.